Hubungan Usia Menarke dan Panjang Tungkai Mahasiswi Umur 18-20 Tahun Fakultas Kedokteran Universitas Hang Tuah Surabaya Semester 1 Tahun Ajaran 2017/2018 - Qonnytah JH; Riami (HANG TUAH MEDICAL JOURNAL, 2019)
ABSTRACT Background : According to the WHO, menarche is the first menstruation in adolescente. The most important event occuring in teenage girls is their first period caled the menarche. Menarch is a culmination of a series of change in an adult woman. In women, menarche marks a transition to adulthood, a sign that teenage daughters have now become a woman and can assume the duties and responsibilities of an adult woman. Aim : This study aims to find the relationship between the age of menarche and leg length of female students of hang tuah medical faculty in their first semester, attending the 2017/2018 academic year. Material and Methods : This research uses a survey method for research subjects by filling questionaires and the measurement is done by the researcher. The population includes 58 female students from first semester medical faculty of hang tuah university students as much as 221 people consisting of 83 male students and 139 female students. The technique of determining sample uses a simple random sampling technique. Data of menarche is obtained by distributing questionaires and the data on leg length is acuired by measurement by the researcher using a measuring tape with prescision of 0,1 cm. Results : The result of the research found that there is no correlation between age of menarke with length of student's leg UHT FK semester 1 academic year 2017/2018, proved by value of Sig. = 0.479 (> 0.05). Conclusion :The conclusion that can be taken from this research is that there is no correlation between menarche age of menarke with length of student's leg UHT FK semester 1 academic year 2017/2018